Political control of bureaucracy in India - Jain, R.B. (1998)
Discussing briefly the concept of political control of bureaucracy in general and in the specific Indian context, the author elaborates on the available mechanisms - both traditional as well as new - in this regard, namely, legislative, internal, Public Interest Litigation, and transfer of officials. He then highlights the emerging issues of political control of bureaucracy through posing searching questions. In view of the ethical dilemmas involved in pursuing functional rationality, the author concludes cautioning responsible administrators to guard against forces which may influence them to act otherwise through developing an inner sense of responsibility. - Reproduced
Keywords: Bureaucracy - India; Bureaucracy